Methodology for the quantitative determination of fenbendazole and its metabolites in organs and tissues of animals by high performance liquid chromatography with tandem mass spectrometry detection - A. I. Varlamova (Российский паразитологический журнал, 2021)
The purpose of the research is to develop a methodology for the quantitative determination of fenbendazole (FBZ) and its metabolites in organs and tissues of sheep by high performance liquid chromatography tandem mass-spectrometry (HPLC-MS/MS).Materials and methods. The method for determining of FBZ and its metabolites after the administration of the supramolecular complex of fenbendazole was validated in accordance with international guidelines for the following indicators: linearity, recovery, specificity, precision, accuracy, limits of quantitative and qualitative determination.Results and discussion. The method of quantitative analysis of FBZ and its metabolites sulfone and sulfoxide in the body of sheep after the administration of the supramolecular complex has been adapted. The proposed method has a linear relationship (R > 0.99) in the range of 5–1000 ng / g and has shown a good reproducibility and accuracy.